The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/jo030354j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Phthalocyanines with Eight Benzylchalcogeno Substituents from 5,6-Dibromo-4,7-diethylbenzo[1,2,3]trichalcogenoles

Abstract: Benzo[1,2,3]trichalcogenoles with two bromine atoms on the benzene ring, 5,6-dibromo-4,7-diethylbenzo[1,2,3]trichalcogenoles (1a) and (1b) (chalcogen: 1a = S; 1b = Se), were first prepared by treating 2,3,5,6-tetrabromo-1,4-diethylbenzene (TBDEB) with elemental sulfur or amorphous selenium in DBU at 140 degrees C (for 1a) and 100 degrees C (for 1b) for 24 h. The structures of 1a and 1b were verified by NMR spectroscopy, mass spectrometry, and elemental analysis. X-ray crystallographic analysis ultimately showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…X-ray crystallographic analysis showed that 3 has a monoclinic form and the space group is P2 1 /n (#14) with parameters a = 11.5476 (8), b = 18.4177 (16), c = 16.9028 (15) Å, and β = 92.878 (3)°. It appears that the unit cell consists of two molecules of 3.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray crystallographic analysis showed that 3 has a monoclinic form and the space group is P2 1 /n (#14) with parameters a = 11.5476 (8), b = 18.4177 (16), c = 16.9028 (15) Å, and β = 92.878 (3)°. It appears that the unit cell consists of two molecules of 3.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…[6,7] In a related study, we recently reported the preparation, structural determination, and optical and electrochemical properties of octaethyloctakis-(benzylthio)phthalocyanine and octaoctyltetrakis(trithiolo)-phthalocyanine and their derivatives. [8] On the other hand, it is known that tetraazaporphyrins fused to four five-membered heterocycles such as furans, pyrroles, and thiophenes are extremely unstable, although these compounds can be considered as isosteric structures of phthalocyanine. [9] Despite many early attempts to prepare tetraazaporphyrins with four five-membered heterocycles, up to now only tetra(2,3-thieno)tetraazaporphyrin (2,3-TTTAP) bearing four thiophene units linked at their 2,3-positions and several related compounds have been reported as stable derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[15] To improve the synthetic procedure for phthalonitrile, we tried to introduce the o-xylylene group on the sulfur atoms as a protecting group. Compound 1a was treated with sodium borohydride and potassium carbonate in THF/methanol, and then with α,αЈ-dibromo-o-xylene to give 4,5-dibromo-3,6-diethyl-1,2-(o-xylylenedithio)benzene (2a) in 77 % yield.…”
Section: Preparation Of Tetrakis(o-xylylenedithio)phthalocyaninesmentioning
confidence: 99%
“…[21] In contrast, peripheral modification of phthalocyanines through the S-C bond cleavage of thioethers is rare. [15] Deprotection and subsequent functionalization of 4b, 4c, and 4b-Ni was thus tried. Typically, the four o-xylylene groups of 4c were removed under argon by treatment with lithium metal in THF/liquid ammonia at -78°C for 1 h (Scheme 4).…”
Section: Deprotection and Functionalization Of 4b 4c And 4b-nimentioning
confidence: 99%
See 1 more Smart Citation